«Ревизор» Н. Гоголя в переводоведческой парадигме Майкла Бересфорда - Краснобаева, Оксана Дмитриевна; Krasnobayeva, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2016)
Исследована проблема популяризации инонационального классического гоголевского наследия в рецепции британского лингвиста М. Бересфорда. Его переводческий труд проникнут заботой о рецепции текста «Ревизора» современным английским читателем во всей его идейно-художественной целостности, с учетом накопленного мировым гоголеведением интерпретационного опыта, и вносит существенный вклад в разработку типологии изданий классических текстов, практику текстологии и переводоведения. Бересфорд концептуализирует теоретические проблемы текстологической и переводческой парадигмы гоголевской пьесы, актуализирует комплексный характер исследования гоголевского текста во всей полноте его содержательной и функциональной парадигмы, что обусловливает перманентное исследование принципов изучения раннего драматического наследия Н. Гоголя в иноязычном переводческом дискурсе. The problem of Gogol’s classic heritage popularization in the reception of Britain linguist M. Beresford is investigated. His work of theory of translation is filled with attention to reception of the text «The Government Inspector» by present-day English reader in all its ideological and art integrity, taking into account interpretative experience which is saved up by world knowledge of Gogol, and makes a significant contribution to the development of a typology of classical texts editions, practice of textual criticism and theory of translation. Beresford conceptualizes theoretical problems of a textual and translation paradigm of Gogol’s play, updates the comprehensive study of Gogol’s text in all its fullness of its substantial and functional paradigm, resulting in permanent study of the principles of studying early dramatic Gogol’s heritage in a translation discourse.
N. Gogol’s «The Government Inspector» in a Theory of Translation Paradigm of Michael Beresford
Keywords: рецепция; переводоведение; интерпретация; инонациональный; парадигма; reception; theory of translation; interpretation; of other nationalities; paradigm